2005
DOI: 10.1542/peds.2004-1176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Infant Feeding on the Risk of Obesity Across the Life Course: A Quantitative Review of Published Evidence

Abstract: Initial breastfeeding protects against obesity in later life. However, a further review including large unpublished studies exploring the effect of confounding factors in more detail is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
696
11
44

Year Published

2005
2005
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 962 publications
(783 citation statements)
references
References 71 publications
32
696
11
44
Order By: Relevance
“…Finally, compared with being bottle-fed, being breast-fed was associated with slightly lower levels of weight gain and obesity (50) . The epidemiological evidence was found to be substantial and generally consistent (55,56) . The review did not address whether consumption of fast foods, intake of non-caloric sweeteners and breast-feeding influenced inflammation concomitantly with BMI.…”
Section: Nutrients and Physical Activitymentioning
confidence: 88%
“…Finally, compared with being bottle-fed, being breast-fed was associated with slightly lower levels of weight gain and obesity (50) . The epidemiological evidence was found to be substantial and generally consistent (55,56) . The review did not address whether consumption of fast foods, intake of non-caloric sweeteners and breast-feeding influenced inflammation concomitantly with BMI.…”
Section: Nutrients and Physical Activitymentioning
confidence: 88%
“…96 The critical window for hypernutrition may extend further into postnatal life, as numerous clinical studies, summarized in systematic reviews and meta-analyses, 33,[97][98][99] have shown that rapid weight gain during early infancy is associated with susceptibility to obesity in adulthood. Such rapid weight gain is often associated with formula feeding, and some [100][101][102] but not all 103 observational studies and metaanalyses have found that breast-feeding is protective against obesity in later life. Similarly, studies that have manipulated the composition of formula feeds have shown protective effects of slower growth against later cardiovascular risk factors in adolescence.…”
Section: The 'Early-life Hypernutrition' Pathwaysmentioning
confidence: 99%
“…Evidence for the long-term effects of infant nutrition on later health (1) has given impetus to the need to develop methods for assessing the diets of populations of infants. Previous studies in Europe and the USA have mainly used estimated or weighed records to assess diet at around 6 months (2)(3)(4)(5)(6)(7)(8) .…”
Section: Infants Food Frequency Questionnaire Weighed Diary Dietary Imentioning
confidence: 99%